2009
DOI: 10.1128/jb.00202-09
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Bacillus subtilis Divergent yetL and yetM Genes by a Transcriptional Repressor, YetL, in Response to Flavonoids

Abstract: DNA microarray analysis revealed that transcription of the Bacillus subtilis yetM gene encoding a putative flavin adenine dinucleotide-dependent monooxygenase was triggered by certain flavonoids during culture and was derepressed by disruption of the yetL gene in the opposite orientation situated immediately upstream of yetM, which encodes a putative MarR family transcriptional regulator. In vitro analyses, including DNase I footprinting and gel retardation analysis, indicated that YetL binds specifically to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…Binding of the aromatic ligand releases the repressor from the promoter and leads to the induction of the regulated gene(s). Structurally, the reported aromatic ligands range from salicylate (MarR) [18], 3-chlorobenzoate [19], 2-methylhydroquinone [20] to flavonoids [21]. The genes encoding MarR proteins are generally part of the gene cluster that they regulate and are divergently oriented to them.…”
Section: Introductionmentioning
confidence: 99%
“…Binding of the aromatic ligand releases the repressor from the promoter and leads to the induction of the regulated gene(s). Structurally, the reported aromatic ligands range from salicylate (MarR) [18], 3-chlorobenzoate [19], 2-methylhydroquinone [20] to flavonoids [21]. The genes encoding MarR proteins are generally part of the gene cluster that they regulate and are divergently oriented to them.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in our previous studies and described here, B. subtilis is the first Gram-positive bacterium that was demonstrated to possess multiple flavonoidresponsive transcriptional regulatory systems, 21,32) while it was also reported that, in addition to the NodD system, rhizobia that are classified as Gram-negative bacteria possess the other transcriptional regulatory systems in response to flavonoids. 33,34) The LmrA/QdoR system is first characterized in the genus Bacillus as the system that utilizes flavonoids as an effector molecule for the transcriptional induction of their regulon.…”
Section: Conclusion and Prospectsmentioning
confidence: 93%
“…These DNA-binding motifs consist of the internal region of each subunit, and their N and C termini are intertwined with each other to form a core domain. As YetL dimerization in solution was confirmed by gel filtration, 32) it is assumed that YetL shares this structural feature.…”
mentioning
confidence: 99%
See 2 more Smart Citations